(Phenylseleno)acetic acid based precursor for the regiospecific synthesis of 1-phenylseleno-2-alkanones*. Issue 9 (19th May 2022) - Temperini, Andrea; Ballarotto, Marco; Siciliano, Carlo
Abstract: A new procedure for the regiospecific synthesis of 1-(phenylseleno)alkan-2-ones starting from (phenylseleno)acetic acid has been developed. When (phenylseleno)acetyl chloride, generated from the corresponding acid, was allowed to react with phenylthio(alkyl)cuprate(I) reagents, 1-(phenylseleno)alkan-2-ones were obtained in fair to good yields. Graphical Abstract: UF0001